3
$\begingroup$

Finding $\displaystyle \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln\bigg(\frac{1+x}{1-x}\bigg)dx$

Try: Let $$\displaystyle I = \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln\bigg(\frac{1+x}{1-x}\bigg)dx$$ (Function is even )

$$I = 2\int^{1}_{0}\bigg[\ln(1+x)-\ln(1-x)\bigg]\frac{x^3}{\sqrt{1-x^2}}dx$$

Using By parts

$$I = 2\bigg[\ln\bigg(\frac{1+x}{1-x}\bigg)\bigg(\sqrt{1-x^2}-\sqrt[3]{1-x^2}\bigg)\bigg]\bigg|^{1}_{0}+4\int^{1}_{0}\frac{1}{1-x^2}\cdot \bigg(\sqrt{1-x^2}-\sqrt[3]{1-x^2}\bigg)dx$$

Could some help me to solve second Integration, Thanks

$\endgroup$
  • 2
    $\begingroup$ Maybe you need Beta function. $\endgroup$ – Szeto Sep 29 '18 at 9:35
  • $\begingroup$ It is $$\frac{5\pi}{3}$$ $\endgroup$ – Dr. Sonnhard Graubner Sep 29 '18 at 9:51
  • $\begingroup$ There's an error in your by-part turning the $\frac{x^3}{\sqrt{1-x^2}}dx$ into its anti-derivative $\endgroup$ – Lee David Chung Lin Sep 29 '18 at 10:05
3
$\begingroup$

Since $\int \frac{x^3}{\sqrt{1-x^2}} \, dx = -\frac{1}{3}(2+x^2)\sqrt{1-x^2}$, integration by parts yields

\begin{align*} \int_{-1}^{1} \frac{x^3}{\sqrt{1-x^2}} \log\bigg(\frac{1+x}{1-x}\bigg) \, dx &= \int_{-1}^{1} \frac{2(2+x^2)}{3\sqrt{1-x^2}} \, dx. \end{align*}

Now the substitution $x = \sin\theta$ quickly yields the answer $\frac{5}{3}\pi$.

$\endgroup$
2
$\begingroup$

Let us consider your integral: $$I = \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln\bigg(\frac{1+x}{1-x}\bigg)dx$$ Separate the integral: $$I= \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1+x)\ dx-\int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1-x)\ dx$$ Consider the right-hand integral. Let $x=-t$ such that $dx=-dt$, where $t\in (1,-1)$: $$I= \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1+x)\ dx-\int^{-1}_{1}\frac{(-t)^3}{\sqrt{1-(-t)^2}}\ln (1-(-t))\ (-dt)$$ Incorporate a minus sign into the integral in order to switch to interval to $t\in (-1,1)$: $$I= \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1+x)\ dx+\int^{1}_{-1}\frac{t^3}{\sqrt{1-t^2}}\ln (1+t)\ dt$$ Recognize that $t$ is a dummy variable. Let $t=x$ such that $dt=dx$, where $x\in (-1,1)$: $$I= \int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1+x)\ dx+\int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1+x)\ dx=2\int^{1}_{-1}\frac{x^3}{\sqrt{1-x^2}}\ln (1+x)\ dx$$ Apply integration by parts: $$I=-\frac{2}{3}\sqrt{1-x^2}(x^2+2)\ln(1+x)\bigg|^{1}_{-1}+\frac{2}{3}\int^{1}_{-1}\sqrt{1-x^2}\frac{x^2+2}{1+x}\ dx=\frac{2}{3}\int^{1}_{-1}\sqrt{1-x^2}\frac{x^2+2}{1+x}\ dx$$ Let $x=\sin(u)$ such that $dx=\cos(u)\ du$, where $u\in (-\pi/2,\pi/2]$: $$I=\frac{2}{3}\int^{\pi/2}_{-\pi/2}\cos^2(u)\frac{\sin^2(u)+2}{1+\sin(u)}\ du=\frac{2}{3}\int^{\pi/2}_{-\pi/2}(\sin^2(u)+2)\frac{1-\sin^2(u)}{1+\sin(u)}\ du$$ Perform long-division on the integrand: $$I=\frac{2}{3}\int^{\pi/2}_{-\pi/2}(\sin^2(u)+2)(1-\sin(u))\ du=\frac{2}{3}\int^{\pi/2}_{-\pi/2}\sin^2(u)\ du-\frac{2}{3}\int^{\pi/2}_{-\pi/2}\sin^3(u)\ du+\frac{4}{3}\int^{\pi/2}_{-\pi/2}du-\frac{4}{3}\int^{\pi/2}_{-\pi/2}\sin(u)\ du$$ Since $\sin^3(u)$ and $\sin(u)$ are odd, their integrals evaluate to zero. Rewrite $\sin^2(u)$ by making use of a double-angle identity: $$I=\frac{1}{3}\int^{\pi/2}_{-\pi/2}(1-\cos(2u))\ du+\frac{4}{3}\int^{\pi/2}_{-\pi/2}du=\frac{5}{3}u-\frac{1}{6}\sin(2u)\bigg|^{1}_{-1}$$ Thus, $$I=\frac{5}{3}\pi$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.